Amelioration of acute myocardial infarction by saponins from flower buds of Panax notoginseng via pro-angiogenesis and anti-apoptosis. (2nd April 2016) - Yang, Bin-Rui; Cheung, Kwok-Kuen; Zhou, Xin; Xie, Rui-Fang; Cheng, Pei-Pei; Wu, Shen; Zhou, Zhong-Yan; Tang, Jing Yi; Hoi, Pui Man; Wang, You-Hua; Lee, Simon Ming-Yuen
Abstract: Ethnopharmacological relevance: The root of Panax notoginseng is traditionally used as an anti-hemorrhagic agent to promote blood circulation without causing "congealed" blood. Furthermore, the flower of P. notoginseng is a popular, traditional medicine taken daily for the preventing of hypertension and for reducing blood cholesterol profiles. Besides, the flower of P. notoginseng contains a higher level of saponins, particularly protopanaxadiol-type ginsenosides, as compared to the root. However, detailed pharmacological studies on this flower have rarely been conducted. Material and methods: In this study, the saponins extracted from the flower of P. notoginseng (FS) were examined on the endothelial cell migration assay, chemically induced vascular insufficiency model in zebrafish larvae and myocardial infraction (MI) model in rats, for determination of their pro-angiogenic and therapeutic effects on MI treatment. Results: Our results demonstrate that FS significantly promoted VEGF-induced migration of human umbilical vein endothelial cells (HUVECs) and partially restored defective intersegmental vessels (ISV) in a chemically induced vascular insufficiency model of zebrafish larvae. When compared to MI group, two weeks post-treatment of FS (25–50 mg/kg/day) induced approximately 3-fold upregulation of VEGF mRNA expression and a concomitant increase in blood vessel density in the peri-infarct area of the heart. Moreover, TUNEL analysis indicates a reduction in the mean apoptotic nuclei per field in peri-infarct myocardium upon FS treatment. Conclusions: The pro-angiogenic effects of FS demonstrated in in vitro and in vivo experimental models suggest that the purified saponin preparation from flowers of P. notoginseng may potentially provide preventive and therapeutic agent for cardiovascular diseases. Graphical abstract: